“Relación entre la enfermedad pulmonar obstructiva crónica sobreinfectada y la periodontitis” - Jimmy Omar, Llamuca Colcha (2020)
This research is intented to analyze the influence of periodontitis in exacerbated chronic obstructive pulmonary disease. The study of research correspond to a descriptive, exploratory, correlational, field, transversal and non-experimental process. As data collection techniques, the observation and analysis of documents were applied and their instruments were reports of the results of C-reactive protein (CRP) and spirometry. The study sample consisted of 14 reports of CRP and pulmonary function before and after periodontal treatment, which were donated by the physical breathing department of the “Modern Basic Hospital”. The observed results indicated that the CRP present in chronic diseases, decreases considerably and there was an improvement in the lung function of the patients by significantly decreasing the bacterial load of the oral cavity, statistically significant differences were found between the value of the Tiffeneau index before and after periodontal treatment (p= 0.001) and similarly between the value of the CRP before and after periodontal treatment (p= 0.00).